Pengaruh Menggambar Bertahap terhadap Pengembangan Kreativitas pada Anak Kelompok B di RA Sunan Ampel - Muhsinin Muhsinin (Program Studi PGRA, 2019)
In this study, the main problem is the creativity of children in drawing has not developed as expected. Efforts to overcome this, research has been carried out which aims to determine how much influence the gradual drawing of the creativity of children in group B RA SunanAmpelTongasProbolinggo. The method of this research is qualitative descriptive type. The subjects were children in group B which numbered 15 children enrolled in the 2018-2019 school year. Data collection techniques through observation, interviews and documentation, then the data is analyzed qualitatively. The results of the research on Day 1 observations draw Triangle, Square, and Circle Patterns of 1 child (5%) BSB, there are 2 children (10%) BSH, there are 3 children (15%) MB, and 14 children (70%) BB. Observation on the second day Free drawing from the basic form Triangle, square, circle there is 1 child (5%) BSB, there are 2 children (10%) BSH, there is 1 child (5%) MB, and there are 16 children (80%) BB . Observation Day III Draw cats from the basic triangle pattern, square and circle 5 children (25%) BSB, there are 9 children (45%) BSH, there are 3 children (15%) MB, and there are 3 children (15%) BB. From the above research, it can be concluded that there is the effect of gradual drawing on the creativity of children in group B at RA SunanAmpel until the third meeting.